Impact of high body mass index on allograft outcomes in kidney transplant recipients with presensitization to human leukocyte antigen - Park, Yohan; Lee, Hanbi; Ko, Eun Jeong; Lee, Sua; Ban, Tae Hyun; Min, Ji-Won; Yoon, Hye-Eun; Oh, Eun-Jee; Yang, Chul Woo; Chung, Byung Ha (Kidney research and clinical practice, 2021)
This study aimed to investigate whether high body mass index (BMI) and presensitization to human leukocyte antigen (HLA) in kidney transplant recipients (KTRs) affected allograft outcomes.BACKGROUNDThis study aimed to investigate whether high body mass index (BMI) and presensitization to human leukocyte antigen (HLA) in kidney transplant recipients (KTRs) affected allograft outcomes.From January 2010 to December 2018, 1,290 kidney transplantations (KTs) were performed at the Seoul St Mary's Hospital. Of these, 682 cases of ABO-compatible living donor KT patients were enrolled. They were divided into four groups (low BMI-non-sensitized, high BMI-non-sensitized, low BMI-sensitized, and high BMI-sensitized) according to the median BMI value (22.7 kg/m2) and HLA presensitization status (anti-HLA antibody mean fluorescence intensity > 3,000). Short-term and long-term allograft outcomes were compared between groups.METHODSFrom January 2010 to December 2018, 1,290 kidney transplantations (KTs) were performed at the Seoul St Mary's Hospital. Of these, 682 cases of ABO-compatible living donor KT patients were enrolled. They were divided into four groups (low BMI-non-sensitized, high BMI-non-sensitized, low BMI-sensitized, and high BMI-sensitized) according to the median BMI value (22.7 kg/m2) and HLA presensitization status (anti-HLA antibody mean fluorescence intensity > 3,000). Short-term and long-term allograft outcomes were compared between groups.In the high BMI-sensitized group, the decline in allograft function was higher than that in the other three groups. Death-censored graft loss (DCGL) rates were highest in the high BMI-sensitized group (4 of 21 [19.0%], p = 0.04). In the multivariable Cox regression hazard regression model analysis, the hazard ratio (HR) for DCGL was intensified when high BMI and presensitization statuses were combined (HR, 3.75; p = 0.03); these statuses significantly interacted with each other (p-value for interaction = 0.008).RESULTSIn the high BMI-sensitized group, the decline in allograft function was higher than that in the other three groups. Death-censored graft loss (DCGL) rates were highest in the high BMI-sensitized group (4 of 21 [19.0%], p = 0.04). In the multivariable Cox regression hazard regression model analysis, the hazard ratio (HR) for DCGL was intensified when high BMI and presensitization statuses were combined (HR, 3.75; p = 0.03); these statuses significantly interacted with each other (p-value for interaction = 0.008).Our results suggest that presensitization to HLA and high BMI might have an interactive adverse impact on allograft outcomes in KTRs.CONCLUSIONOur results suggest that presensitization to HLA and high BMI might have an interactive adverse impact on allograft outcomes in KTRs.